Respuesta :

[tex] \gray \bigstar \boxed{\angle 1 + \angle 2 + \angle 3= 180°}[/tex]

Reason :-

Sum of angles of triangle is equal to 180°

Formula :-

  • sum = (no. of angles - 2) × 180°
  • Sum = (3 - 2) × 180°
  • Sum = 1 × 180°
  • Sum = 180°

[tex] \\ \\ [/tex]

So:-

[tex] \\ [/tex]

[tex] \sf \dashrightarrow\angle 1 + \angle 2 + \angle 3= 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow m + 3m +(m - 35) = 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow m + 3m +m - 35= 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 4m +m - 35= 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 5m - 35= 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 5m= 180 \degree + 35 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 5m=215\degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow m= \dfrac{215}{5} \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow m= \cancel \dfrac{215}{5} \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \bf \dashrightarrow m=43 \degree[/tex]

[tex] \\ \\ [/tex]

Verification :-

[tex] \\ [/tex]

[tex] \sf \dashrightarrow m + 3m +(m - 35) = 180 \degree[/tex]

put value of m

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 43 + 3(43) +(43 - 35) = 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 43 + 3(43) +(8) = 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 43 + 3(43) +8= 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 43 +129+8= 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \sf \dashrightarrow 43 +137= 180 \degree[/tex]

[tex] \\ \\ [/tex]

[tex] \bf \dashrightarrow 180 \degree= 180 \degree[/tex]

LHS = RHS

Hence verified!

ACCESS MORE